Centennial fever transnational Hispanic commemorations and Spanish nationalism - Moreno Luzón, Javier 1967- (Studies in Latin American and Spanish history, 2024)
"Commemorations that shaped major elements of Spanish identity at the beginning of the 20th century are full of centennials and anniversaries that elaborate and renew the Spanish national mythology. In Centennial Fever Javier Moreno-Luzón, one of the most prominent Spanish historians of his generation, studies the milestones that defined transnational dimensions of celebration at the beginning of the 20th century including the Peninsular War, the first Spanish Constitution, the independence of Latin American States, the "discovery" of the Pacific Ocean and the death of Miguel de Cervantes and the publication of Don Quixote of La Mancha. Through these truly global events, a cultural community is created, called "Hispanoamerica" or "La Raza", on which Spanish nationalism has become dependent"--